(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Stress Management has become a most important and valuable technique to boost the employee morale and the company’s productivity in all companies. All the Organizations have understood that the employees play a key role and they should be out of stress to give a high performance atmosphere. There are varieties of techniques to manage stress in organizations. High stress jobs refer to work, which involves hectic schedule and complex job responsibilities that result into imbalance between personal and work life. Overwork may affect physical health of individual resulting into ineffective work and dissatisfaction-among employees leading to imbalance in family or personal life also. Due to improper job role assignment, improper working conditions, underutilization of skills and organizational politics the employees could be stressed. There are lots of individualstress like role ambiguity, psychological hardiness, and type of personality that affect the morale of the employees as a whole.